2018
DOI: 10.3389/fpsyg.2018.01472
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Relationship With Their Pet Dogs and OXTR Genotype Predict Child–Pet Interaction in an Experimental Setting

Abstract: Human–animal interaction (HAI) research has increasingly documented the important role of pet dogs in children’s lives. The quality of interaction between children and their pet dogs, however, is likely influenced by individual differences among children as well as their perceived relationship with their pet dog. Ninety-seven children aged 7–12 years and their pet dogs participated in a laboratory protocol during which the child solicited interaction with their dog, from which time petting and gazing were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The 13 studies in the Research Topic employed a wide range of measures, including salivary cortisol to assess Hypothalamic Pituitary Adrenal (HPA) axis reactivity and stress levels (Pendry et al, 2018;Pan et al, 2019), survey questions (Bures et al, 2019), and a genetic assay to look at the relationship between a single polymorphism in the oxytocin receptor and individual differences in response to HAI activities (Kertes et al, 2018).…”
Section: Measures and Methodologymentioning
confidence: 99%
“…The 13 studies in the Research Topic employed a wide range of measures, including salivary cortisol to assess Hypothalamic Pituitary Adrenal (HPA) axis reactivity and stress levels (Pendry et al, 2018;Pan et al, 2019), survey questions (Bures et al, 2019), and a genetic assay to look at the relationship between a single polymorphism in the oxytocin receptor and individual differences in response to HAI activities (Kertes et al, 2018).…”
Section: Measures and Methodologymentioning
confidence: 99%
“…Although there has been limited empirical research in this area, there is some evidence to suggest that OXTR genotype (possibly affecting the expression of the oxytocin receptor and thus sensitivity to oxytocin) is linked with natural variation in interactions with dogs. For example, Kertes et al [ 188 ] examined whether the OXTR genotype was related to children’s perceived relationships and their petting and gazing behaviors with pet dogs. Simulating naturally occurring HAI in the context of a laboratory experiment, the results of this study indicated that variation at the OXTR polymorphism rs53576 was associated with the proportion of time spent petting during child–pet interactions, but not gazing behaviors.…”
Section: Social Relationships the Stress Response And Perinatal Mental Healthmentioning
confidence: 99%
“…Such findings complement other research documenting that children with anxiety disorders tend to interact with a pet dog for long durations and have fewer interactions with other people compared to children with other behavioral health problems [ 194 ]. Although there is significant need for replication of the Kertes et al [ 188 ] study in child and adult samples, this suggests that pets (i.e., dogs) may be important sources of social interaction for individuals with socioemotional difficulties or challenges connecting with other humans. Moreover, OXTR genotype may be a biomarker that warrants attention in studies examining the role of HAI in perinatal health.…”
Section: Social Relationships the Stress Response And Perinatal Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations